2003
DOI: 10.3748/wjg.v9.i3.516
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of water-induced coccoidHelicobacter pyloriand its experimental infection in mice

Abstract: Although the virulence of coccoid H. pylori induced by water decrease, coccoid H. pylori still remains a considerable urease activity and the adhering ability to epithelial cells. Furthermore, the flagella, an important component responsible for bacterial movement and infection, were still observed as a cellular structure of coccoid H. pylori under electron microscope. The coccoid H. pylori induced by water is capable of colonizing in gastric mucosa and causing gastrititis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 31 publications
2
61
1
2
Order By: Relevance
“…As H. pylori is a human pathogen, it is possible that the VBNC form is more infectious in humans than in mice. Further, we only exposed mice to one strain of H. pylori , and it is possible that other strains would be more infectious in the VBNC state than SS1, as has been seen in other published papers in the literature 19, 27. Despite our large sample sizes and high doses, our inability to infect mice with VBNC H. pylori via drinking water suggests that VBNC SS1 in water is not infectious in mice.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…As H. pylori is a human pathogen, it is possible that the VBNC form is more infectious in humans than in mice. Further, we only exposed mice to one strain of H. pylori , and it is possible that other strains would be more infectious in the VBNC state than SS1, as has been seen in other published papers in the literature 19, 27. Despite our large sample sizes and high doses, our inability to infect mice with VBNC H. pylori via drinking water suggests that VBNC SS1 in water is not infectious in mice.…”
Section: Discussionmentioning
confidence: 95%
“…She et al 19. found that 11 of 16 mice gavaged with VBNC H. pylori were infected compared to 14 of 16 gavaged with the same dose of viable, culturable H. pylori .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations